IMPROVING TEACHER PERFORMANCE ON PARTICIPATE IN TRAINING AND ACADEMIC SUPERVISION - Sukatmin Sukatmin (Universitas Islam Negeri (UIN) Sumatera Utara, 2020)
The entire population was made sample research. The research instrument for training variables and academic supervision is a poll with a Likert scale model, while the teacher's performance is used APKG I and APKG II. The requirements test is done to test the normality, linearity, and independence between the free variables. The data analysis techniques used correlation and regression and simple correlation and regression and double correlation at the level of significance 0.05. The results clarify that there is a significant influence on training activities, academic supervision towards improvement of teacher's performance.